PEMBERIAN DEDAK PADI HASIL FERMENTASI TERHADAP PERTUMBUHAN CACING SUTERA (Tubifex sp.) MENGGUNAKAN SISTEM RESIRKULASI - Laheng, Suardi; Putri, Ika Wahyuni; Riskasari, Riskasari (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2019)
In this research, we investigated the effects of supplementation of rice bran fermented with Effective Microorganism (EM4) on the biomass of tubifex worms cultured in the recirculation system. A Completely randomized design was made, consisting of 4 treatments and 3 replications. The experimental animals were treated with different types of feed, i.e. (A) unfermented rice bran, three times a day; (B) fermented rice bran, three times a day; (C) fermented rice bran, 5 times a day; (D) fermented rice bran, 7 times a day. They were reared in a wood box (100 Ã— 50 Ã— 15 cm3), while a mixture of fermented rice bran and mud was applied as their growth medium. Tubifex worms were grown in the medium at a density of 100 g/m2, and supplemented with fermented rice bran at a dose of 500 g/box, with various frequency levels of 3, 5 and 7 times a day. Biomass of the worm and water quality was observed. As a result, we found that the addition of fermented rice bran at a rate of 5 times a day (treatment C) exhibited the greatest biomass growth, reaching up to 104,33 g/m2.